Conceptual Aspects of Development Banks - Alekseevna Bunich, Galina; Aleksandrovich Rovenskiy, Yuriy; Tambievna Akhvlediani, Julia; Anatolievna Zvonova, Elena (International Journal of Engineering and Technology, 2018)
The development of national and regional economies in the conditions of financial and economic instability determines special conditions for the formation of financial resources.The innovative improvement of national economies of developing countries has substantiated active evolvement of financial institutions such as development banks.The formation and evolvement of development banks is going through a new phase. These are not the financial institutions that were formed by the metropolis countries after the collapse of the colonial system. They have different mission, goals, principles, methods and instruments.Modern development banks prioritize the issues of financing socio-economic projects, crediting traditional sectors of the economic activity, and, above all, the infrastructure development of regions, the construction of transport systems, and energy supply. Today one of the most important areas of the development banksâ€™ credit activity is the formation of a loan portfolio for small and medium-sized businesses.With all the diversity of development banks substantiated by historical and economic characteristics of countries and regions, the UNO and the World Bank Group distinguish common features, principles and peculiarities. These peculiarities and unique functions of development banks are found in international standards that define a special status of development banks as financial institutions.Â